ANALISA PENGARUH DUKUNGAN ATASAN, KETERLIBATAN KERJA, LAMA DI ORGANISASI DAN USIA PADA JOB CONTENT PLATEAUING - Djamilah, Siti (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2005)
This research examined the influence of supervisor support, job involvement, age and organizational tenure on job content plateauing. This research tested to lecturers in Economic Faculty of Wijaya Kusuma University Surabaya. Fifty questionnaires were distributed, 46 questionnaires returned and only 45 questionnaires were able to be used. Next step, the researcher examined validity and reliability testing which delivered independent variabel: those were supervisor support and job involvement. Beside that, it delivered dependent variabel that was job content plateauing. Multiple regressions was used to examined the effect of four variabel toward job content plateauing. The result of multiple regressions indicated that the effect of supervisor support and job involvement toward job content plateauing were supported. In the other hand, the result of multiple regression proved that organizational tenure and age had no influenceon job content plateauing.